DEKONSTRUKSI PERBUATAN AKHLAKI AKUNTAN PROFESIONAL BERBASIS TRANSFORMASI DIRI “NAFS” - Ida Ayu Nursanty (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
Ethical dilemmas arise as a consequence of conflicts audit because the auditor is in a situation of decision-making between ethical and unethical. The situation in the conflict are formed because there are parties interested in the auditor's decision, which auditors faced with a decision between ethical and unethical. Thus the focus of this study is how an accountant take the right decision. With the concept of self-transformation